Influence of Additional Feeding Recovery on The Intellectual Intelligence of Children - Widyyati, Mei Lestari Ika; Irwanto, Irwanto; Adi, Annis Catur (Health Notions, 2018)
Nutrition is the main requirement for a toddler, if not obtained food according to needs its nutrition value, it will interfere with the growing swell of current or next time. The purpose of this research was to analyze the effect of Additional Feeding Program Recovery on the intellectual intelligence children aged 4-5 years. Design of this research was observational cohort retrospective. The sample size was 70, were divided into two groups, group with a history of getting Additional Feeding Recovery and the Group didnt get Additional Feeding Recovery. Independent variable was Additional Feeding Recovery and the dependent variable was intellectual intelligence. Data was analyzed using Independent Sample t-test. There was no difference in the level of intelligence on the two group with p-value = 0.129. Kewords: Additional feeding recovery, Intellectual intelligence